ANALISIS GAYA KEPEMIMPINAN DALAM PENGELOLAAN BUMDes DESA LALANG LUAS KECAMATAN V KOTO KABUPATEN MUKO MUKO - Zulkarnain, Zulkarnain; Adriadi, Rekho (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
Lalang Luas Village in V Koto District, Muko Muko Regency, has a Village-Owned Enterprise (BUMDes) in the plantation sector, namely oil palm plantations as a business unit. However, the management did not go well because the funds available for management were not utilized properly. The aim of this research is to determine the leadership style in managing BUMDes in Lalang Luas Village, V Koto District, Muko Muko Regency. The method used in this research is a qualitative method with a descriptive approach. The results of the research show that BUMDes leaders in leading BUMDes in Lalang Luas Village have not completely gone well. Where BUMDes leaders do not dare to make decisions so that the existing funds for BUMDes management are not utilized as well as possible. Then, the lack of responsibility of leaders in leading BUMDes so that BUMDes business units are not managed well and the lack of knowledge and experience of BUMDes leaders also influences the less than optimal management of BUMDes. Keywords: Leadership Style, BUMDes, Lalang Luas Village